Optimized Kalpha x-ray flashes from femtosecond-laser-irradiated foils - Lu, W; Nicoul, M; Shymanovich, U; Tarasevitch, A; Zhou, P; Sokolowski-Tinten, K; von der Linde, D; Masek, M; Gibbon, P; Teubner, U (Physical review. E, Statistical, nonlinear, and soft matter physics, 2009)
We investigate the generation of ultrashort Kalpha pulses from plasmas produced by intense femtosecond p-polarized laser pulses on Copper and Titanium targets. Particular attention is given to the interplay between the angle of incidence of the laser beam on the target and a controlled prepulse. It is observed experimentally that the Kalpha yield can be optimized for correspondingly different prepulse and plasma scale-length conditions. For steep electron-density gradients, maximum yields can be achieved at larger angles. For somewhat expanded plasmas expected in the case of laser pulses with a relatively poor contrast, the Kalpha yield can be enhanced by using a near-normal-incidence geometry. For a certain scale-length range (between 0.1 and 1 times a laser wavelength) the optimized yield is scale-length independent. Physically this situation arises because of the strong dependence of collisionless absorption mechanisms-in particular resonance absorption-on the angle of incidence and the plasma scale length, giving scope to optimize absorption and hence the Kalpha yield. This qualitative description is supported by calculations based on the classical resonance absorption mechanism and by particle-in-cell simulations. Finally, the latter simulations also show that even for initially steep gradients, a rapid profile expansion occurs at oblique angles in which ions are pulled back toward the laser by hot electrons circulating at the front of the target. The corresponding enhancement in Kalpha yield under these conditions seen in the present experiment represents strong evidence for this suprathermal shelf formation effect.